The conflict between indigenous communities and corporations at the intersection of politics and economics in Southeast Asia - Ahmad Harakan (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
This article investigates the confluence of political and economic factors in the disputes that arise between corporations and indigenous communities in Southeast Asia. The Southeast Asian region has been a locus of considerable contention between corporations and native populations, particularly with regard to the utilisation of natural resources. The conflict is further intensified by the cultural heterogeneity of the region and the intricate social intricacies that ensue from it. The aforementioned conflicts are analysed within a comprehensive framework that encompasses the political and economic milieu at both the regional and national levels. The method used is qualitative, with data sources derived from journal articles, news, reports, and government and interantional organizations publications. Data processing begins with data collection, data analysis, data interpretation, and data visualisation in the form of tables and figures. The findings indicate that the aforementioned conflicts are not solely focused on vying for resources but also encompass a broader struggle for autonomy, personal identity, and basic human entitlements. The aforementioned assertion underscores the noteworthy impact of political and economic variables in moulding and escalating conflicts. It is imperative to establish a conflict resolution mechanism that is both inclusive and sustainable and safeguards the rights and interests of all stakeholders in order to mitigate and potentially resolve the conflict at hand.